Online updating method with new variables for big data streams. Issue 1 (9th August 2017) - Wang, Chun; Chen, Ming‐Hui; Wu, Jing; Yan, Jun; Zhang, Yuping; Schifano, Elizabeth
Abstract: For big data arriving in streams online updating is an important statistical method that breaks the storage barrier and the computational barrier under certain circumstances. In the regression context online updating algorithms assume that the set of predictor variables does not change, and consequently cannot incorporate new variables that may become available midway through the data stream. A naive approach would be to discard all previous information and start updating with new variables from scratch. We propose a method that utilizes the information from earlier data in the online updating algorithm with bias corrections to improve efficiency. The method is developed for linear models first, and then extended to estimating equations for generalized linear models. Closed‐form expressions for the efficiency gain over the naive approach are derived in a particular linear model setting. We compare the performance of our proposed bias‐correcting approach and the naive approach in simulation studies with data generated from a normal linear model and a logistic regression model. The method is applied to a study on airline delay, where reasons for delays were only available more recently, starting in 2003. The Canadian Journal of Statistics 46: 123–146; 2018 © 2017 Statistical Society of Canada